Comparing Radiotherapy alone with Chemotherapy Radiotherapy in Treatment of Patients with Stage II and III Endometrial Cancer - Hamid Rezvani; Hamid Attarian; Naghmeh Fatemi; Ahmad Mosavizadeh; Mahdi Tabarrai (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
Introduction: Endometrial cancer is the most common pelvic malignancy in women. Approximately 7,000 women die from this disease every year. Although most patients can be treated with appropriate therapies, there is insufficient data regarding the choice of the best adjuvant therapy after a surgical procedure in advanced endometrial cancer cases. It seems that radiotherapy or chemotherapy alone don’t provide good survival. The aim of this study was to compare radiotherapy alone with chemotherapy-radiotherapy in the treatment of patients with stages II and III endometrial cancer. Methods: In this study, we selected 34 patients with stages II and III endometrial cancer who had undergone surgery. There were 22 patients in first group who received chemotherapy and 12 patients in second group who received chemotherapy and then radiotherapy with the same dosage as the first group. Mean survival rates and disease free survival rates during a 30-month period were evaluated. Results: Local relapse was noted in 7 of the patients in the first group who had undergone radiotherapy alone, while no relapse was noted in the second group (p=0.03). Distant metastasis was observed in one patient from the first group. The disease free survival in first group was 22.4± 1.2 months. In the second group, whhad undergone radiotherapy after chemotherapy, no relapse or metastasis was observed. There was no significant difference regarding between the two groups serious adverse effects. Conclusions: This study showed that radiotherapy after chemotherapy is an effective method of treatment for patients with stages II and III endometrial cancer and is not associated with significant adverse effects.